Las Naciones Unidas en un mundo postnacional - Tomassini, Luciano (Estudios Internacionales, 1995)
This paper aims not to make an evaluation of the United Nations Organization fifty years after its creation, but to compare the mission originally conferred on the world organization with the characteristics and demands that local and global societies present today in a post-national world, always taking into account how the political and socio-economic functions of the organization are balanced. This true "change of an era" presents a new scenario in which the relationship between the States and the global community has been modified, so it is necessary to carry out an epistemological change to adapt the United Nations to the impending post-national world.